IMPLEMENTASI ALGORITMA K-NEAREST NEIGHBOR UNTUK IDENTIFIKASI KUALITAS AIR (STUDI KASUS : PDAM KOTA SURAKARTA) - Rio Adi Arnomo; Wawan Laksito Yuly Saptomo; Paulus Harsadi (STMIK Sinar Nusantara, 2018)
Water quality in urban areas in Surakarta has decreased nowadays. The increase of industrial development, its poor sewage treatment, and some other factors cause this urban problem. The result of the water quality monitoring system with K-Nearest Neighbor algorithm on this research certainly will help the laborers’ duty of PDAM (Local Government Owned Water Utilities) in analyzing water quality. For the consideration of majority output in this method, the system works by taking the nearest distance to the assigned number of K. The training data for this research was taken in March 2016 form the report of water monitoring result in PDAM’S laboratory of Surakarta. The identification result is divided into eligible (MS) and ineligible (TMS). The testing data result is applied in algorithm performance testing with confusion matrix having accuracy level 82,5%.Keywords: water quality, K-Nearest Neighbor, Confusion matrix